Pengaruh Pendidikan Kesehatan dengan Media Leaflet terhadap Pengetahuan tentang Preeklampsia pada Kader Kesehatan di Desa Kuwiran Kecamatan Banyudono Boyolali - Anis Afri Nurul Hudha; Sri Handayani (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Background: Hypertension in pregnancy is the leading cause of maternal death due to preeclampsia in pregnancy. Preeclampsia screening in the maternal and child health (MCH) book can be done by cadres. The eradication program involving cadres has not run optimally this is because there are still few cases of pregnancy with preeclampsia detected by Health cadres. Good knowledge is expected to increase cadre action in order to conduct early detection of preeclampsia. Data from the Banyudono Health Center showed that the detection rate of high risk by the community in December 2023 was 10.9%, still far from the target of 20%. Puskesmas Banyudono consists of 6 villages where the village with the most high-risk pregnancies is Kuwiran Village, namely 107 (32.7%) pregnant women in 2023. The purpose of the study was to determine the effect of health education with leaflet media on knowledge about preeclampsia in health cadres in Kuwiran Village, Banyudono Boyolali District. This research design is a pre-experiment with a one group pre-test post-test design. The population of this study were all health cadres in Kuwiran Village, Banyudono Boyolali District in June 2024, totaling 31 respondents. The sampling technique used in this study was total sampling, the research instrument used SAP, leaflets and questionnaires. Data analysis with Wilcoxon. Research results: The age of most cadres is more than 35 years, namely 25 respondents (80.6%), the education is mostly secondary, namely 22 respondents (71.0%), the majority are working, namely 23 respondents (73.2%), the knowledge of health cadres before The majority of health education had sufficient knowledge, namely 16 respondents (51.6%), after health education was in the good category, 20 respondents (64.5%). Statistical test results with Wilcoxon p-value 0.000 <0.05. Conclusion: There is an influence of health education using leaflet media on knowledge about early detection of preeclampsia among health cadres in Kuwiran Village, Banyudono Boyolali District.